Method Of Using The Steam Approach In Teaching Biology - Jumabayev Abdulkhamid Tokhtanazarovich (Euro Asian Journal Publishing, 2024)
This article discusses the theoretical and practical foundations of using the STEAM approach in teaching biology. The article examines in detail the relevance of this approach, methods that can be used in biology lessons, projectbased learning methods, and innovative solutions aimed at solving problems.
Keywords: STEAM; biology education; interdisciplinary integration; problem-based learning